Teprotumumab in the management of thyroid eye disease mechanistic insights and adverse reactions: a comprehensive review - Xu, Zhibin; Hu, Nan; Chen, Qitao; Zhou, Yue; Huang, Yunye; Hu, Songhao; Jin, Haoru; Tang, Yubo (Frontiers in Endocrinology, 2025)
Teprotumumab has shown significant efficacy in treating Thyroid Eye Disease (TED), but its adverse effects require careful management. Key reactions include hearing impairment, hyperglycemia, and potential exacerbation of pre-existing inflammatory bowel disease (IBD). Hearing impairment, likely due to inhibition of the insulin-like growth factor 1 receptor (IGF-1R), manifests as more severe sensorineural changes. Hyperglycemia results from disrupted growth hormone feedback and may be worsened by prior glucocorticoid use. Although teprotumumab does not appear to induce new diabetes cases, it can exacerbate existing hyperglycemia. Cognitive issues, infusion reactions, and other adverse effects, such as muscle cramps and weight loss, have also been observed. Management requires careful patient screening, particularly for those with histories of hearing loss, diabetes, or IBD. Further research is essential to elucidate the underlying mechanisms of these adverse effects and develop targeted preventive strategies to improve the safety and efficacy of teprotumumab in clinical practice.